Adolescent presentations to an adult hospital emergency department. (2nd August 2017) - Noori, Omar; Batra, Shweta; Shetty, Amith; Steinbeck, Katharine
Abstract: Objective: Age‐related policies allow adolescents to access paediatric and adult EDs. Anecdotally, paediatric and adult EDs report challenges when caring for older and younger adolescents, respectively. Our aim was to describe the characteristics of an adolescent population attending an adult ED, co‐located with a tertiary paediatric ED. Methods: The Westmead Hospital ED database was accessed for 14.5–17.9 years old presentations between January 2010 and December 2012. Patient diagnosis coding (SNOMED) was converted to ICD‐10. De‐identified data were transferred into Microsoft Excel with analysis performed usingspss V22. Results: There were 5718 presentations made to the Westmead Hospital, Sydney, Australia ED by 4450 patients, representing 3.3% (95% CI 3.2–3.4) of total visits from all patients 14.5 years and above. The mean age of the sample was 16.6 years (male 51.8%). Presentations triaged as level 4 or 5 represented 61.0% (95% CI 58.7–61.3) of visits. The proportion of patients who did not wait to receive care was 13.8% (95% CI 12.9–14.7), which was significantly higher than adult rates ( P < 0.01). There were 279 unscheduled return visits (visits made <72 h of discharge) representing 4.9% (95% CI 4.4–5.8) of all presentations. Injury was the most common diagnosis (30.2%, 95% CI 28.8–31.6). Chronic physical illness and alcohol‐related visits comprised 2.1% (95% CI 1.7–2.5) and 0.8% (95% CI 0.6–1.0) of adolescent presentations, respectively. Conclusion: Contrary to reported staff perceptions, adolescent chronic physical illness presentations were not a major burden. Alcohol was likely under‐recorded as a contributing factor to presentations.